A Val66Met polymorphism is associated with weaker somatosensory cortical activity in individuals with cerebral palsy. Issue 9 (September 2022) - Trevarrow, Michael; Sanmann, Jennifer N.; Wilson, Tony W.; Kurz, Max J.
Abstract: Background: The brain-derived neurotrophic factor (BDNF) protein plays a prominent role in the capacity for neuroplastic change. However, a single nucleotide polymorphism at codon 66 of the BDNF gene results in significant reductions in neuroplastic change. Potentially, this polymorphism also contributes to the weaker somatosensory cortical activity that has been extensively reported in the neuroimaging literature on cerebral palsy (CP). Aims: The primary objective of this study was to use magnetoencephalography (MEG) to probe if BDNF genotype affects the strength of the somatosensory-evoked cortical activity seen within individuals with CP. Methods and procedures: and Procedures: Twenty individuals with CP and eighteen neurotypical controls participated. Standardized low resolution brain electromagnetic tomography (sLORETA) was used to image the somatosensory cortical activity evoked by stimulation of the tibial nerve. BDNF genotypes were determined from saliva samples. Outcomes and results: The somatosensory cortical activity was weaker in individuals with CP compared to healthy controls (P = 0.04). The individuals with a Val66Met or Met66Met BDNF polymorphism also showed a reduced response compared to the individuals without the polymorphism (P = 0.03), had higher GMFCS levels (P = 0.04), and decreased walking velocity (P = 0.05). Conclusions and implications: These results convey that BDNF genotype influences the strength of the somatosensory activity and mobility in individuals with CP. What this paper adds: Previous literature has extensively documented altered sensorimotor cortical activity in individuals with CP, which ultimately contributes to the clinical deficits in sensorimotor processing documented in this population. While some individuals with CP see vast improvements in their sensorimotor functioning following therapeutic intervention, others are clear non-responders. The underlying basis for this discrepancy is not well understood. Our study is the first to identify that a polymorphism at the gene that codes for brain derived neurotrophic factor (BDNF), a protein well-known to be involved in the capacity for neuroplastic change, may influence the altered sensorimotor cortical activity within this population. Potentially, individuals with CP that have a polymorphism at the BDNF gene may reflect those that have difficulties in achieving beneficial outcomes following intervention. Thus, these individuals may require different therapeutic approaches in order to stimulate neuroplastic change and get similar benefits from therapy as their neurotypical peers. Abstract : Sensorimotor; Lower extremity; Brain imaging; Neuroplasticity; Neurogenetics.